2014
DOI: 10.4236/msce.2014.21002
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Modification of Carbon Nanotubes with Biocompatible Polylactic Acid

Abstract: Polylactic acid (PLA) was successfully covalently grafted onto multi-walled carbon nanotubes (MWCNT) by microwave-assisted polymerization of lactide monomers. The final products MWCNT-g-PLA were characterized with Fourier-transform IR (FTIR), Raman spectroscopy, thermogravimetric analyses (TGA) and transmission electron microscopy (TEM). The results indicated PLA chain was covalently attached to the MWCNT. The grafted PLA was uniformly coated on the surface of MWCNT with a layer thickness of 2 ~ 6 nm. The graf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Hence it can be inferred that the thermal stability will significantly increased proportional to the decomposition temperature; the more the carboxyl group bonded to the MWCNTs, the higher the decomposition temperature. A mass loss of COOH functionalized MWCNTs reported at 460 ˚C associated with the successful functionalization [24][25]. The higher the concentration makes more MWCNTs being digested in the process.…”
Section: Resultsmentioning
confidence: 99%
“…Hence it can be inferred that the thermal stability will significantly increased proportional to the decomposition temperature; the more the carboxyl group bonded to the MWCNTs, the higher the decomposition temperature. A mass loss of COOH functionalized MWCNTs reported at 460 ˚C associated with the successful functionalization [24][25]. The higher the concentration makes more MWCNTs being digested in the process.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature [34], although I D /I G is a factor affecting the electrochemical activity during the discharge process, other factors such as the specific surface area, pore size and pore volume can be considered as one of the other important factors affecting the specific capacitance. Based on the XRD and Raman analyzes, it could be initially suggested that the superior electrochemical properties in terms of specific capacitance of PK800M with I D /I G =1.01 are achieved by the microwave reflux treatment, which causes a favorable change in the crystal structure of the sample [36][37][38].…”
Section: Physical and Chemical Characterization Of Activated Carbonsmentioning
confidence: 99%